Elevated prevalence of high-risk HPV in healthy oral mucosa of users and nonusers of drugs in Northeastern Brazil - Ribeiro, Mariana Goveia Melo; Marcolino, Larissa Doddi [UNESP]; Ramos, Bruna Ribeiro de Andrade [UNESP]; Trento, Cleverson Luciano; Araujo, Karina Conceição Gomes Machado de; Silva, José Rodrigo Santos; Jain, Sona; Gurgel, Ricardo Queiroz; Silva, Márcia Guimarães [UNESP]; Dolabella, Silvio Santana (FapUNIFESP (SciELO), 2019)
Variable rates of HPV infection have been reported in healthy oral mucosa worldwide. The main objective of this study was to detect and genotype HPV infection in users and nonusers of drugs with clinically healthy mucosa from the Northeast Brazil. Samples from 105 patients were amplified using the primers MY09/MY11 and GP5+/GP6+, and genotyping was performed by multiplex-PCR for HPV-6/11, 16 and 18. A total of 81.9% samples were positive. Among drug users, 84.5% presented the virus and 20.4% showed multiple infections. Among non-drug users, 78.7% were positive and 13.5% had multiple infections. Limited information is available on oral HPV in Brazilian population, especially for drug users, and our results showed higher HPV infection rates in both users and nonusers of drugs. More studies and researches focused on drug users including factors like sexual behavior, nutrition and cultural habits are necessary to enhance the comprehension of this relationship, and develop preventive strategies.